Social partnership «school – family – community» in the anti-bullying activity with the school youth in Canada - Костюк, Ольга Олександрівна (Pedagogy of Higher and Secondary Education, 2017)
In this article we present an analysis of the partnership among such agents as school, family and community in the anti-bullying activity with Canadian school youth. Our work is based on the research conducted by Canadian scholars, educational documents and information on anti-bullying programs and strategies available at Canadian school websites, community organizations’ web pages, etc.The article looks at the issue starting from a description of numerous ministries’ responsibilities in bullying prevention (the Ontario Ministry of Education, the Ministry of Training, Colleges and Universities, the Ministry of Community Safety and Correctional Services, the Ministry of Tourism and Recreation, the Ministries of Children and Youth Services/Community and Social Services/Health and Long-Term Care. Next, we proceed to present peculiarities of cooperation between schools and families directed towards tackling bullying. It has been concluded that educators and parents constantly stay in contact, make joint decisions. The Parent Council is involved in the school anti-bullying plan development, school antibullying extra-curricular projects, which are especially actively realized the National Bullying Awareness Week and the Random Acts of Kindness Week. In addition, parents are expected to fill in the questionnaire on the school climate.The article reviews community involvement (community organizations,community members and activists, celebrities, police officers etc.) in antibullying projects. The focus here is on restorative justice practices, anti-bullying initiatives and projects across Canada (campaigns, programmes, presentations, workshops, contests, conferences, excursions, hackathons, video shooting, writing poems, stories, articles, bookmarks and badges creation, anti-bullying software and mobile applications development, flash mobs performance, peer facilitation, the Student Council activity), anonymous help line services to report bullying, a national online anti-bullying campaign, anti-bullying programmes which are provided or supported by the community. In many respects Canadian bullying prevention strategies present a scientific interest and a practical value. After a meticulous examination they can be implemented in Ukrainian schools.